Fast track opportunities for high achievers? A comparative investigation into career advancement patterns for in-house and consultancy practitioners - Wolf, Katharina (Routledge Taylor and Francis Group, 2010)
Public relations and communication graduates usually extensively debate the "pro and cons" of the industry's two key employment options. To date there has been a lack of research into potential differences in required skills sets, career advancement and promotional opportunities between these two employment types. Contrary to management research, public relations scholars have largely focused on traditional career advancement determinants, such as experience in years and gender, largely failing to embrace modern management research into career advancement. Based on previous research into alternative career advancement factors, which has highlighted the importance of social competencies and networking skills for PR practitioners, this paper sets out to investigate potential differences in career advancement factors and career development patterns for in-house and consultancy-based practitioners.